PENGGUNAAN ALGORITMA LINEAR REGRESSION UNTUK PREDIKSI HARGA SMARTPHONE BERDASARKAN SPESIFIKASINYA - Fonga, Riistan Riana; Ratnasari, Silvia (CV SWA Anugerah, 2025)
Smartphones are a communication tool that is needed by today's society to support its activities. In the current digital era, the variety and number of smartphones available on the market is very large, making it difficult for consumers to determine the price according to the desired specifications. This research aims to predict smartphone prices based on their specifications using the Linear Regression algorithm. By processing the data using the Rapidminer tool, to determine the performance of the algorithm, the data is divided, namely by dividing the training data by 80% and testing data by 20%. The data used for research is a dataset taken from the Kaggle site with the title mobile price prediction dataset. From the results of testing and modeling the linear regression algorithm with a data division of 80:20, the RMSE results were 182,637 +/- 0.000, the RMSE and Relative Error values were close to 0, indicating that the predictions were close to the actual values. The recommendation that can be given to future researchers is to try using other data mining algorithms in the prediction process to find out the comparison of performance and accuracy between the various methods used. Smartphone merupakan alat komunikasi yang dibutuhkan oleh masyarakat saat ini dalam menunjang aktivitasnya. Dalam era digital saat ini, variasi dan jumlah smartphone yang tersedia di pasaran sangat banyak, sehingga mempersulit konsumen dalam menentukan harga yang sesuai dengan spesifikasi yang diinginkan. Penelitian ini bertujuan untuk memprediksi harga smartphone berdasarkan spesifikasinya menggunakan algoritma Linear Regression. Dengan pengolahan data menggunakan tools Rapidminer, untuk mengetahui kinerja algoritma tersebut maka dilakukan pembagian data yakni dengan pembagian data training sebanyak 80% dan data testing sebanyak 20%. Data yang digunakan untuk penelitian adalah dataset yang diambil dari situs kaggle dengan judul dataset mobile price prediction. Dari hasil pengujian dan pemodelan algoritma linear regression dengan pembagian data 80:20, mendapatkan hasil RMSE 182.637 +/- 0.000, nilai RMSE dan Relative Error yang mendekati 0 menunjukan bahwa prediksi mendekati nilai aktual.